Issue of the boundaries between good and evil in theological-moral discourse - Balák, René (Studia Nauk Teologicznych PAN, 2021)
Hardly any problem in contemporary theological-moral discourse causes such turbulence as the searching, reflection, and demarcation of the boundaries between good and evil in human acting. A fundamental problem is a criterion or a reference point according to which a person could reliably determine what is good and evil. Divergent theological views in the theological-moral dimension seem to have caused the clear boundaries between good and evil to disappear. Therefore, the crucial question is whether there is still a universal criterion for theological evaluation of a human act, as the situation in theological-moral discourse resembles an areopagus of opinions that have no common point in distinguishing between good and evil. This reflection examines the possibility if the Thomistic ethical analysis of a human act, together with the principle of double effect, may be a reference point for the demarcation of these boundaries.